Program Pendampingan Pengurusan Legalitas Produk bagi KWT Bengke Sakato Pengolah Kelapa di Kabupaten Padang Pariaman - Wenny Surya Murtius; Neswati Neswati; Gunarif Taib; Sahadi Didi Ismanto; Novelina Novelina; Vioni Derosya; Purnama Dini Hari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2019)
These activity partners are members of the women farmer (KWT) group whose activities are centered on processing coconut fruit into a variety of coconut-derived products. Among the coconut derivative products produced by KWT are VCO, coconut oil and nata de coco. Product legality is a standard that has become a reference for consumers in buying a product. Producers who want their products to be known and have more value in the eyes of consumers must meet these standards. Among the legality of products that become consumers' reference are P-IRT, Halal, BPOM, SNI and so on. The activity was carried out using the andragogy method (counseling and hands-on practice). This activity involved several parties who were directly related to this program. The results of the activity showed that KWT was very enthusiastic and immediately made improvements to several things suggested by the licensing agency, including the use of equipment and production layouts. It was concluded that this KWT will immediately obtain BPOM licensing so as to increase the selling value and the amount of VCO product sales.